Electrochemical bases of macrorunning in of flat friction surfaces process at ECMP(G) - Замота, Т.Н. (Problems of Tribology, 2014)
The results of theoretical researches of electrochemical-mechanical running in are presented in the article. The mathematical model, describing diminishing of macrogeometrical error of flat surfases at ECMR, is got.